Psychological Resistance and Emotional Processing in Women with Repeated Abortions: A Predictive and Comparative Study in the Light of Some Demographic Variables - Ismail , Ramadan Mohamed (Journal of Ecohumanism, 2025)
Psychological Resistance and Emotional processing in Women Repeat Abortion: A Predictive and Comparative Study in the Light of Certain Demographic variables. The study aims to identify the relationship between psychological resistance and emotional processing in a sample of women repeaters of abortion and to reveal the degree to which psychological resistance contributes to the prediction of emotional processing in the study sample, There are also statistically significant differences in psychological resistance and emotional processing among women with repeated abortions due to variables demographic (age, number of times of abortion, presence of chronic diseases), study relied on the comparative correlative descriptive curriculum, and the study sample consisted of 94 women suffering from repeated abortions at Suzanne Women’s and Childbirth University Hospital in Minya governorate, and the study tools included the psychological resistance scale, prepared by Wafaa Imam ( 2017); the Emotional processing scale (Prepared by the researcher ) and the study’s findings found a statistically significant (positive) correlation between psychological resistance and emotional processing in women with repeated abortions, and found predictability of emotional processing in women with repeated abortions through psychological resistance. It also found statistically significant differences in psychological resistance and emotional processing in women with repeated abortions attributable to demographic variables (age, number of times of abortion, presence of chronic diseases).